4-Phenylbutyrate Prevents Endoplasmic Reticulum Stress-Mediated Apoptosis Induced by Heatstroke in the Intestines of Mice. Issue 1 (July 2020) - Cao, Yan; Liu, Zhifeng; Xiao, Weiwei; Gu, Zhengtao; Xiao, Guizhen; Yuan, Fangfang; Chen, Fang; Pei, Yanfang; Li, Hui; Su, Lei
ABSTRACT: Objective: Heatstroke can induce serious physiological dysfunction in the intestine. However, the underlying mechanisms of this condition are unknown, and therapeutic strategies are not available. In this study, we explored the role of endoplasmic reticulum (ER) stress signaling in this process and assessed whether pretreating mice with an inhibitor of ER stress could alleviate intestinal damage. Methods: A heatstroke model was established in male mice. Mice were pretreated with 4-phenylbutyrate (4-PBA) before exposure to heat stress. Intestinal morphological changes were observed by hematoxylin and eosin (H&E) staining and transmission electron microscopy. The TUNEL assay was used to detect intestinal apoptosis. The expression of the ER stress-related proteins and apoptosis-related proteins was investigated by the Western blot assay. Results: Compared with control group, mice with heatstroke exhibited evidence of intestinal injury and epithelial apoptosis, accompanied by significantly increased expression of ER stress-related proteins in the intestines. The intestinal injury score and level of intestinal epithelial apoptosis were significantly reduced after administration of 4-PBA. Furthermore, the levels of the intestinal ER stress-related proteins GRP78, PERK, p-eIF2α, ATF4, and CHOP were decreased after 4-PBA treatment. Conclusions: Our results indicate that the ER stress-mediated apoptosis pathway is activated during heat stress-induced intestinal injury. 4-PBA can inhibit heatstroke-induced intestinal ER stress and attenuate intestinal injury. We provide evidence that the beneficial effect of 4-PBA is closely related to the inhibition of ER stress-mediated apoptosis. These findings suggest that ER stress may be a novel therapeutic target in patients with heatstroke.